2012
DOI: 10.1002/chem.201200744
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer in an Amine–Corrole–Perylene Bisimide Assembly: Charge Separation over Terminal Components Favoured by Solvent Polarity

Abstract: An assembly has been synthesised that consists of four units: a meso-substituted corrole (C3), perylene bisimide (PI), and two electron-rich triphenylamine (DPA) units. PI is connected through a 1,4-phenylene bridge to C3, whereas the two DPA units are linked to C3 through a diphenyl ether linkage, which is used for the first time to connect the various moieties. Various synthetic strategies were elaborated, and the chosen one afforded the final system in six steps in an overall yield of 6 %. The resulting ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…The CVs recorded for corroles 4 and 9 are shown as typical examples in Figure 3. All corresponding oxidation and reduction half‐wave potential values ( E 1/2 ) are listed in Table 3 together with those of 5,10,15‐trispentafluorophenylcorrole ( Tpfc ), 5,10,15‐tris(4‐methylphenyl)corrole ( TTc ),37 and 10‐(4‐methylphenyl)‐5,15‐(pentafluorophenyl)corrole ( C3 ) measured under the same experimental conditions 38. Each CV features two irreversible reduction waves and up to three irreversible oxidation waves (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CVs recorded for corroles 4 and 9 are shown as typical examples in Figure 3. All corresponding oxidation and reduction half‐wave potential values ( E 1/2 ) are listed in Table 3 together with those of 5,10,15‐trispentafluorophenylcorrole ( Tpfc ), 5,10,15‐tris(4‐methylphenyl)corrole ( TTc ),37 and 10‐(4‐methylphenyl)‐5,15‐(pentafluorophenyl)corrole ( C3 ) measured under the same experimental conditions 38. Each CV features two irreversible reduction waves and up to three irreversible oxidation waves (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…as typical examples in Figure3.A ll corresponding oxidation and reduction half-wave potentialv alues (E 1/2 )a re listed in Ta ble 3t ogether with those of 5,10,15-trispentafluorophenylcorrole (Tpfc), 5,10,15-tris(4-methylphenyl)corrole (TTc), [37] and 10-(4-methylphenyl)-5,15-(pentafluorophenyl)corrole (C3)m ea-sured under the same experimental conditions. [38] Each CV features two irreversible reduction waves and up to three irreversible oxidation waves (Figure 3). Previous studies of the electrochemical properties of corrole free bases have shown that their redox behavior is rather complicated because the starting compounds, written as CorH 3 ,u ndergo facile gain or loss of inner protons.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most‐studied green dyes are fluoresceins, Oregon green 488 and 514, perylene diimide, the rhodamine green family, chlorophyll, and eosin . Red dyes typically come from rhodamines, porphyrins, and corroles …”
Section: Introductionmentioning
confidence: 99%
“…However, for this assembly a very efficient light energy collection on the corrole chromophore was detected; for details, see the original paper 61. Next, the structure DPA‐C3‐PI was synthesized (Figure b), which was somehow similar to the previous case but missing the extended conjugation of the terminal aromatic amine electron donor 62. This increases the HOMO–LUMO gap of the unit and makes it easier to oxidize.…”
Section: Systems For Charge Separation Based On Corrolesmentioning
confidence: 93%